The questions of progress of amateur chorus performance and foims of its organization in the modern terms (Pedagogy of Higher and Secondary Education, 2007)
In this article the historical aspect of origin and progress of amateur chorus performance is considered.
Keywords: chorus creation; amateur; amateur chorus group